Analisis Metode Tafsir ayat Al-Qur’an: Kajian Terhadap manuskrip Kitab Bahjat Al-ʻUlūm Karya Abu Layst As-Samarqandi - Birri, Fatkhul; Saifudin, Ahmad; Wijaya, Roma (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractExamining a manuscript will uncover numerous aspects of Islam. The Bahjat Al-ʻUlūm was discovered in Magelang City. This study aims to analyze the verses found in the manuscript of Bahjat Al-ʻUlūm by Abu Layts As-Samarkandi and elucidate the method and style of interpretation used. This study employed a descriptive analysis method with library study. The book Bahjat Al-ʻUlūm discusses the 'ilm al-kalam and includes nine Qur'anic verses. The analysis of these verses reveals that two verses illustrate the muqaddimah (preface); Allah’s trait Al-Razzaq is addressed in the third and fourth verses, belief in the angels is explored in the fifth verse, the names of prophets are mentioned in the sixth verse, the rewards for the believers and disbelievers are discussed in the seventh and eighth verses, and faith is elaborated in the ninth verse. The Quranic verses mentioned serve as a legal foundation. The author has determined that the verses were interpreted using the ijmali approach with a sufhi style.Keywords: Abu Layst As-Samarqandi, Bahjat Al-ʻUlūm, Manuscript, and Interpretation. AbstrakKajian pada sebuah manuskrip akan mengungkapkan berbagai aspek keislaman. Salah satu manuskrip yang ditemukan di Kota Magelang yakni manuskrip Bahjat Al-ʻUlūm. Tujuan penelitian untuk mempelajari ayat-ayat dalam manuskrip kitab Bahjat Al-ʻUlūm karya Abu layts assamarkandi, kemudian menjelaskan mengenai metode dan corak penafsirannya. Penelitian ini menggunakan metode analisis deskriptif dengan studi kepustakaan. Kitab Bahjat Al-ʻUlūm menjelaskan tentang ilmu kalam dan terdapat sembilan ayat Al-Qur’an. Temuan analisis ayat-ayat tersebut yaitu: dua ayat menjelaskan muqaddimah, Sifat Al-Razzaq dibahas pada ayat ketiga dan keempat, iman kepada malaikat dibahas pada ayat kelima, nama-nama nabi dibahas pada ayat keenam, respon orang mukmin dan kafir dibahas pada ayat ketujuh dan kedelapan, dan iman dijelaskan pada ayat kesembilan. Ayat-ayat Alquran yang dikutip dimaksudkan sebagai landasan hukum. Setelah mempelajari ayat-ayat tersebut penulis mengetahui bahwa metode yang digunakan untuk menafsirkan ayat-ayat tersebut adalah metode ijmali dengan corak tafsir shufi. Kata Kunci: Abu Layst As-Samarqandi, Bahjat Al-ʻUlūm, Naskah, dan Tafsir.